The Learning English Website As The Alternative Media To Enhance The Economics Students’ Competence In Learning English - Aisyah Aisyah (JELLE : Journal Of English Literature, Linguistics, and Education, 2021)
Teaching English in Economics students has own uniqueness than others. Since it is not their main competence, most of the students are still seeing English as the “frightening” and boring subject. In other side, they need mastering English in their future job considering that today most jobs in the world need english mastery as their qualification and to support the business running well. So, it challenges the english teacher to empower many media and techniques to attract their interest in learning english. Therefore, the writer decided to discuss how empowering of the English learning website (bbc.co.uk/learningenglish) could enhance the students’ competence in learning English. The design used was classroom action research and the respondents were the first term students of Faculty of Economics and Business UMPP who took the Basic English before taking English for Specific Purposes (English for Accounting, or English for Management, or English for Economics). In collecting data, the reseacher applied some intruments; test, observation, and field notes. Meanwhile to analyze the data, T-Test was used to examine the significant of using the website in improving the students’ competence.From 180 respondents, after examining proccess by using T-Test, it was taken the mean avarage before the treatment; 57.9750 and after the treatment, the mean avarage is 68.9611. it means the mean avarage after treatment is higher than before one.  Based on the result of T-Test, it showed that the value of  T-Statistics 13.840 is bigger than T-table; 1,96 with the significant value 0.000 (less than 0.05). It means that there is significantly different between before treatment and after one.   Keywords: English for Specific Purposes (ESP), Technology-Enhanced Language Learning (TELL), Teaching English in Economics Students